If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4p + 8 = 10p + 2 Reorder the terms: 8 + 4p = 10p + 2 Reorder the terms: 8 + 4p = 2 + 10p Solving 8 + 4p = 2 + 10p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-10p' to each side of the equation. 8 + 4p + -10p = 2 + 10p + -10p Combine like terms: 4p + -10p = -6p 8 + -6p = 2 + 10p + -10p Combine like terms: 10p + -10p = 0 8 + -6p = 2 + 0 8 + -6p = 2 Add '-8' to each side of the equation. 8 + -8 + -6p = 2 + -8 Combine like terms: 8 + -8 = 0 0 + -6p = 2 + -8 -6p = 2 + -8 Combine like terms: 2 + -8 = -6 -6p = -6 Divide each side by '-6'. p = 1 Simplifying p = 1
| -x^2+50x-350=0 | | 8t^2-6t=9 | | x^5-x^4+9x^3-9x^2=0 | | 2x+3=24 | | 5x^2+36x+36=0 | | 6(x-8)-(2x-2)=5x-1 | | .5(20z+18)-8=9(z-3) | | 7x+19y=-3 | | -4c+1=-7 | | 12n-6=4n+10 | | 3(y+-4)+9(y+1)= | | 11m^2-2m=10 | | 4(3+c)=3(c-4) | | 8n-6=10 | | 3t+15=13t | | 7(a+3)=4a | | 10m(4m-9)=30 | | y^2+8y=4 | | 8(w-6)=2w | | 2x-45=43-2 | | 6*(3x-7)-12-4x=9x-(7x+6) | | x-7-7x=5 | | 10u-20=9u-11 | | 3(a+2)=a+12 | | 8s^2-30s+18= | | 16m^2-1=15m | | 2x^2-25x+36=0 | | X^2-1x-1=0 | | 6a^2-19a+15= | | -6n+10=-4n-18 | | 7y-10=5y-2 | | -6x-9y=54 |